A sociological analysis of the experiences of acceptance of Christian gay men within the Methodist Church of Southern Africa (MCSA) in Grahamstown - Sipungu, Thoko Andy (Rhodes University, Faculty of Humanities, Department of Sociology, 2016)
Buffington, Luibhéid, & Guy (2014: 1) argue that "in the contemporary world, our own sexuality and our sense of the sexualities of others colour all aspects of contemporary life, from interpersonal relations to foreign affairs." In line with this statement, this study provides an account of how a person's gay sexuality can possibly colour that person's experience of acceptance by the Methodist Church of Southern Africa (MCSA) in Grahamstown. Samuel Hill (2008: 6) notes that there is an urgent need to create a dialectic between religious and secular discourse with regards to furthering our understanding of sexuality. Thus this thesis seeks to contribute to the body of scholarship that explores and discusses the disjuncture between one's homosexual identity and one's religious identity. Barton (2012: 2) notes that "gay people are often talked about but seldom listened to; rarely are they asked about their own oppression and the individuals and institutions oppressing them." While adopting a qualitative approach utilising interviews to explore the stories of the respondents, this study applies Bourdieu's concepts of field, habitus, social capital and symbolic violence in order to analyse the experiences of acceptance of gay men within the Methodist Church of Southern Africa (MCSA) in Grahamstown. With regard to the use Bourdieu's concepts in the analysis of the experiences, the following dimensions were considered: i) construction of a gay identity within the field of Christianity as represented by the MCSA in this context, ii) the impact the field has on the 'gay habitus', iii) Social capital as an advantageous strategy in constructing a gay identity within the church, and iv) symbolic violence that gay men experience within the church. In analysing the conditions of the acceptance that gay men receive within the church, this study also uses Jacques Derrida's concept of hospitality.
Keywords: Uncatalogued